Work Discipline, Work Motivation and Employee Performance - Bahasoan, Sandra; Baharuddin, Ida (Advances in Human Resource Management Research, 2023)
Purpose: This study examines and determines the impact of work discipline and motivation on employee performance at PT Trans Kalla Makassar. The research hypothesizes that work discipline and motivation positively and significantly affect employee performance. Research Design and Methodology: The study population consists of 321 employees at PT Trans Kalla Makassar, with a sample size of 76 respondents selected using Slovin's formula. Primary data were collected through questionnaires completed by the respondents. Data analysis included descriptive statistics, validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, hypothesis testing using multiple linear regression analysis, t-tests, f-tests, and coefficient of determination tests. Findings and Discussion: The results indicate that work discipline and motivation positively and significantly affect employee performance at PT Trans Kalla Makassar. Specifically, higher levels of discipline lead to better employee performance, and similarly, increased motivation enhances performance. These findings suggest improving work discipline and motivation can significantly boost employee productivity and effectiveness. Implications: The study's findings have important implications for human resource management practices, particularly in developing strategies to enhance employee discipline and motivation. Future research could explore additional factors influencing employee performance and consider longitudinal studies to examine the long-term effects of discipline and motivation on performance.